2021
DOI: 10.3390/ijerph18010296
|View full text |Cite
|
Sign up to set email alerts
|

Home Language Activities and Expressive Vocabulary of Toddlers from Low-SES Monolingual Families and Bilingual Immigrant Families

Abstract: Children from low-SES (socioeconomic status) and minority language immigrant families are at risk of vocabulary difficulties due to the less varied and complex language in the home environment. Children are less likely to be involved in home language activities (HLA) in interaction with adults in low-SES than in higher-SES families. However, few studies have investigated the HLA variability among low-SES, minority language bilingual immigrant families. This longitudinal study analyzes the frequency and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…However, regarding L1, the number of books at home affected vocabulary in conjunction with individual and environmental variables [22]. The "reading input"-how frequently family members read to a child-was positively associated with vocabulary in L2 [11,19,23], but incoherent data were found in L1 (positive association, 11; lack of association, 24).…”
Section: Quantity and Quality Of Language-exposure Measures And Vocab...mentioning
confidence: 98%
See 3 more Smart Citations
“…However, regarding L1, the number of books at home affected vocabulary in conjunction with individual and environmental variables [22]. The "reading input"-how frequently family members read to a child-was positively associated with vocabulary in L2 [11,19,23], but incoherent data were found in L1 (positive association, 11; lack of association, 24).…”
Section: Quantity and Quality Of Language-exposure Measures And Vocab...mentioning
confidence: 98%
“…The effect of active and passive practices on vocabulary production has also been explored. Florit, Baracchetti, Majorano, and Lavelli [23] found that only active-level practices affected children's expressive vocabulary in L2 at 2 years of age, even though L2 was less frequently used in immigrant families with low socioeconomic status (SES). Finally, Leseman [11] confirmed that specific activities, such as storytelling, talking about everyday facts, and reading books, enhanced L1 vocabulary and that home conversations, such as child-caregiver conversations during lunch/dinner, songs, and nursery rhymes, were crucial for promoting L2 vocabulary.…”
Section: Quantity and Quality Of Language-exposure Measures And Vocab...mentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has pointed out, the effect of digital activity on children's language skills depends on how engaging the material is. Digital activity that encourages good parent-child interactions as when conventional materials are used are more effective than having a child passively absorb language-relevant information (Florit et al, 2021). As such, promotion of digital activity for children should consider digital interactions that resemble responses and replies.…”
Section: The Impact Of Covid-19 Pandemic On Bilingual Children's Home...mentioning
confidence: 99%